Monitoring CO2 emissions to gain a dynamic view of carbon allocation to arbuscular mycorrhizal fungi - Slavíková, Renata; Püschel, David; Janoušková, Martina; Hujslová, Martina; Konvalinková, Tereza; Gryndlerová, Hana; Gryndler, Milan; Weiser, Martin; Jansa, Jan (Mycorrhiza, 2017)
Quantification of carbon (C) fluxes in mycorrhizal plants is one of the important yet little explored tasks of mycorrhizal physiology and ecology. 13CO2 pulse-chase labelling experiments are increasingly being used to track the fate of C in these plant-microbial symbioses. Nevertheless, continuous monitoring of both the below- and aboveground CO2 emissions remains a challenge, although it is necessary to establish the full C budget of mycorrhizal plants. Here, a novel CO2 collection system is presented which allows assessment of gaseous CO2 emissions (including isotopic composition of their C) from both belowground and shoot compartments. This system then is used to quantify the allocation of recently fixed C in mycorrhizal versus nonmycorrhizal Medicago truncatula plants with comparable biomass and mineral nutrition. Using this system, we confirmed substantially greater belowground C drain in mycorrhizal versus nonmycorrhizal plants, with the belowground CO2 emissions showing large variation because of fluctuating environmental conditions in the glasshouse. Based on the assembled 13C budget, the C allocation to the mycorrhizal fungus was between 2.3% (increased 13C allocation to mycorrhizal substrate) and 2.9% (reduction of 13C allocation to mycorrhizal shoots) of the plant gross photosynthetic production. Although the C allocation to shoot respiration (measured during one night only) did not differ between the mycorrhizal and nonmycorrhizal plants under our experimental conditions, it presented a substantial part (∼10%) of the plant C budget, comparable to the amount of CO2 released belowground. These results advocate quantification of both above- and belowground CO2 emissions in future studies.
Keywords: Plant Shoots; Photosynthesis; Carbon; oxid uhličitý; Mycorrhizae; Plant Roots; fotosyntéza; mykorhiza; Medicago truncatula; Glomeromycota; kořeny rostlin; výhonky rostlin; 13C isotope labelling; Rhizophagus irregularis; Shade; uhlík; Belowground carbon (C) allocation; Carbon Dioxide